A numerical model on salt migration in a closed unsaturated fine sand column with temperature gradients. - Resurreccion, Augustus C. (Philippine Engineering Journal)
Solute transport in the unsaturated zone in nonisothermal conditions has its important applications in the field of agriculture and groundwater quality modeling. In this research, the phenomena of simultaneous transport of moisture, heat and solute in the unsaturated porous media are formulated by three partial differential conservation equations. Numerical simulation and experimental study on salt migration is carried out in a closed unsaturated fine sand (Toyourra sand in Japan) column. Numerical discretization and solution are performed on the experimental domain with appropriate boundary conditions by iterative Picard technique Galerkin Finite Element Method. Results show that salt, in initial uniform water content and solute concentration, accumulates at the bottom due to heat source by salt precipitation and moisture convention. The characterization of the identified hydraulic parameters with temperature is also discussed.